(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The results of an evaluation process of a degree in teaching strategies implemented with elementary school mathematics teachers in Panama are presented. The degree course involved activities developed over 4 months, based mainly on the problem-solving approach, contextualized activities and processes of reflection on teaching practice. The purpose was to provide teachers with tools for the design, implementation and improvement of their didactic sequences. To evaluate the impact of this degree, the logical model of evaluation was used and the results were analyzed in quantitative and qualitative areas. As a general result, reflective processes were presented and teachers were able to evaluate their teaching abilities, as well as their attitudes and motivations regarding mathematics teaching, strengthening their disciplinary knowledge and didactic reflection.